PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN STRUKTUR MODAL TERHADAP HARGA SAHAM PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021 – 2024 - Nur Erias Fahmawati; Suhendro; Dimas Ilham Nur Rois (JURNAL ILMIAH EDUNOMIKA, 2026)
This study was conducted to analyze and examine the factors influencing stock prices. The variables studied included firm size, profitability, and capital structure. The study population consisted of property and real estate sector listed on the Indonesia Stock Exchange (IDX) for the 2021-2024 period. The data was processed using statistical tools, namely SPSS version 31. The sampling technique used was purposive sampling, with an initial sample size of 92 companies. During the data processing process, several outliers were identified, resulting in 88 valid data sets after removal. Data analysis was conducted using quantitative methods. The results showed that firm size and capital structure had an effect on stock prices, while profitability did not affect the Stock Price. And firm size, profitability and capital structure simultaneously affect the Stock Price. Keywords: firm size, profitability, capital structure, stock price